2015
DOI: 10.1158/1078-0432.ccr-14-1740
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1–MicroRNA126 Epigenetic Circuit Contributes to Esophageal Squamous Cell Carcinoma Growth via ADAM9–EGFR–AKT Signaling

Abstract: Purpose: MicroRNAs (miRNA) are involved in and are controlled by epigenetic regulation, and thereby form a reciprocal regulatory circuit. Using next-generation sequencing (NGS)-based miRNA profiling, this study aimed to discover esophageal squamous cell carcinoma (ESCC)-specific miRNAs and miRNArelated epigenetic modulations.Experimental Design: NGS-based miRNA profiles were generated for four pairs of ESCC tissues and adjacent normal tissues. In situ hybridization was used to assess miRNA expression and its c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 45 publications
7
94
2
Order By: Relevance
“…Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26). However, few previous studies have demonstrated no significant difference in ADAM9 mRNA expression between OSCC and normal tissues, or between oral cancer cell lines and normal oral keratinocytes (9,28), a finding that differs from our results on ADAM9 protein overexpression.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26). However, few previous studies have demonstrated no significant difference in ADAM9 mRNA expression between OSCC and normal tissues, or between oral cancer cell lines and normal oral keratinocytes (9,28), a finding that differs from our results on ADAM9 protein overexpression.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the lack of this correlation in the breast cancer patients also suggests that during the carcinogenesis process miR-126 is post-transcriptionally regulated. Indeed, it has been previously shown that pri-miRNA and mature expression is positively correlated in normal tissue but not in breast tumors [36]. These results suggested a multistep model for miRNA dysregulation.…”
Section: Journal Of Clinical Epigenetics Issn 2472-1158mentioning
confidence: 86%